Health expenditure and economic growth in sub-Saharan Africa: an empirical investigation - Nicholas M. Odhiambo (Development Studies Research, 2021)
In this study, the causal relationship between health expenditure and economic growth is examined using panel data from sub-Saharan African countries for the period 2008–2017. The study decomposes health expenditure into two components: public health expenditure and private health expenditure. In order to establish whether the causal relationship between health expenditure and economic growth depends on a country's level of income, the study divides the studied countries into two groups: low-income countries and middle-income countries. In order to address the omission-of-variable bias, which is associated with some of the previous studies, the study incorporates life expectancy as an intermittent variable between health expenditure and economic growth – thereby creating a system of multivariate equations. Using a panel ECM-based Granger-causality model, the study found that when public expenditure is used as a proxy, a distinct unidirectional causality from health expenditure to economic growth is found to prevail in low-income countries, but no causality is found to exist in middle-income countries. However, when private health expenditure is used, a short-run causality from economic growth to health expenditure is found to prevail in middle-income countries, but no causality is found to exist in low-income countries. Policy implications are discussed.